2020
DOI: 10.3390/en13030671
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Servovalve Pilot Stage Actuated by a Piezo-electric Ring Bender: A Numerical and Experimental Analysis

Abstract: Electrohydraulic servovalves are widely used for precise motion control in aerospace and other industries due to their high accuracy and speed of response. However, commercial two-stage servovalves have several undesirable characteristics, such as the power consumption caused by the quiescent flow (internal leakage) in the pilot stage, and the complexity and high number of parts of the torque motor assembly, which affect the cost and the speed of manufacture. The solution to these problems can help to reduce c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(46 citation statements)
references
References 25 publications
0
46
0
Order By: Relevance
“…In addition, we can calculate the stiffness constants based on Eqs. (1) ~ (11) in MATLAB and also determine the load-displacement relationship, which is regarded as the theoretical analysis result. Fig.…”
Section: Comparison Between the Theoretical Results And The Fem Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we can calculate the stiffness constants based on Eqs. (1) ~ (11) in MATLAB and also determine the load-displacement relationship, which is regarded as the theoretical analysis result. Fig.…”
Section: Comparison Between the Theoretical Results And The Fem Resultsmentioning
confidence: 99%
“…In [7], magnetic fluids are filled in the air gap of a torque motor to suppress the vibration and noise. Besides studying the torque motor, scholars have devised some innovative electro-mechanical converters, such as piezoelectric actuator [8], piezoelectric ring benders [9][10][11], and giant magnetostrictive actuators [12,13] to pursue higher dynamic performance. The common pre-stage hydraulic amplifiers in TSPSVs are spool valves [14], single nozzle flapper valves [15], double nozzle flapper valves [16], jet pipe valves [17] and deflector jet valves [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The most common piezo electric actuators available on the market are ring benders, rectangular benders, piezo-stacks, and amplified piezo-stacks [1]. In previous studies, we demonstrated that ring benders and rectangular benders are suitable for the actuation of the pilot stages of servovalves [4][5][6][7][8]. Concerning ring benders, two of them, mounted in tandem to provide redundancy, were proposed in [4] to actuate, in place of the torque motor, a double nozzle flapper pilot stage; the feasibility of this architecture was assessed using a detailed Simulink model of the hydraulic, mechanical and electrical parts [4].…”
Section: Introductionmentioning
confidence: 99%
“…Concerning ring benders, two of them, mounted in tandem to provide redundancy, were proposed in [4] to actuate, in place of the torque motor, a double nozzle flapper pilot stage; the feasibility of this architecture was assessed using a detailed Simulink model of the hydraulic, mechanical and electrical parts [4]. In [5,6], we proposed and studied a novel pilot stage configuration composed of two normally closed two-way twoposition (2/2) valves actuated by two piezo-electric ring benders, achieving very good step and frequency response in addition to minimizing the internal leakage. Again, a Simulink model was instrumental in assessing this novel architecture [5,6]; the comparison between the results of the simulations and the experimental data showed that this simulation approach provides very good accuracy [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation